Getting the best out of enterprise systems - Wagner, Erica (Henry Stewart Talks, 2011)
State of affairs, Are enterprises systems different?, Getting the best out of ES, Abandonment?, Late state changes, Selective engagement of users, Resource allocation, Piecemeal implementation, Suggestions and acknowledgements